Challenges in the participatory development of indicators for sustainable beach tourism - Queiroz, Monique Torres de (2024)
Beaches comprise a socio-ecological system that can be affected by various human activities, including tourism. The proposition of sustainability indicators for management is an important tool to reduce their impacts and contribute to environmental quality and recreational experience, either through the calculation of Carrying Capacity (CC) or environmental monitoring. Considering Ecosystem-Based Management, the participatory development and evaluation of management tools have been central elements in the pursuit of sustainability. However, efforts to promote co-construction spaces may not guarantee participation, requiring greater understanding. In this context, this study aims to broaden the scientific debate on the participatory construction of CC indicators on tourist beaches and the situations that may influence it, using the Community-Based Tourism (CBT) initiative of Couves Island and Picinguaba village (Ubatuba, SP, Brazil) as a case study. Through a literature review, field visits, and dialogues with local actors, the impacts related to CBT activities were systematized, and associated indicators proposed. The critical analysis of the applicability of indicators to CC revealed subjectivity in potential implementation but also highlighted the potential of alternative management strategies to mitigate impacts, leading to the development of a decision tree to support the activity, without necessarily altering the number of visitors. The resistance presented by local actors in contributing to the process, which had not been previously anticipated, was investigated through interviews and revealed the influence of contextual aspects, such as personal and institutional misunderstandings before and during the participatory process, and the historical conflict relationship with environmental public policies in the region. It is concluded that the participatory discussion of potentially controversial management tools like CC, which can affect the income of people in already vulnerable communities, should consider the historical context and existing relationships among social actors as well as management alternatives that seek to reduce the impacts of tourism and avoid increased restrictions.